Decoding chicken growth regulation through multi-omics insights and emerging genetic tools for growth optimization - Ali Hassan Nawaz; Jiqiang Ding; Munwar Ali; Dong Leng; Nasir Mukhtar; Ahtisham Ali; Chungang Feng (Poultry Science, 2025)
Body weight and growth are crucial traits in chickens, regulated by an intricate genetic architecture that remains challenging to understand completely. Multiple quantitative trait loci (QTL) mapping and genome-wide association studies (GWAS) have revealed numerous genetic variations associated with these economically important traits, but the application of these findings for sustainable and efficient poultry production is limited. This review synthesizes existing knowledge on the genetic regulation of chicken growth, challenging the traditional approach and encouraging the development of integrated strategies to comprehend the regulatory mechanisms underlying complex growth phenotypes. This review highlights recent advances in omics studies (genomics, transcriptomics, proteomics, and metabolomics), emphasising the utility of single-cell RNA sequencing (scRNA-seq) in addressing cellular heterogeneity within growth-related tissues. The advancement of genome sequencing technologies, combined with progress in CRISPR/Cas9-mediated genome editing, has opened new avenues for the precision breeding of economically important traits in chickens. It also discusses how the newly developed Chicken Genotype-Tissue Expression (ChickenGTEx) project and other related data resources could potentially serve as crucial tools to reveal the regulatory mechanisms related to chicken growth, offering insights into tissue specific gene expression. By elucidating regulatory networks and identifying key knowledge gaps, this review intends to accelerate the development of precision breeding approaches for sustainable and efficient poultry production, ultimately enhancing global food security.